2017
DOI: 10.1111/resp.13017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diabetes mellitus on the clinical presentation and treatment response in tuberculosis

Abstract: DM adversely affected the clinical presentation and treatment response of TB, but there was no difference in the drug resistance and relapse rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 29 publications
0
26
2
1
Order By: Relevance
“…[11][12][13][14] Recent studies in Pakistan have shown more unfavourable outcomes among DS-TB patients with DM; 15,16 however, we could not find any relevant study examining the effect of DM on treatment outcomes among DR-TB patients in Pakistan.…”
contrasting
confidence: 47%
See 1 more Smart Citation
“…[11][12][13][14] Recent studies in Pakistan have shown more unfavourable outcomes among DS-TB patients with DM; 15,16 however, we could not find any relevant study examining the effect of DM on treatment outcomes among DR-TB patients in Pakistan.…”
contrasting
confidence: 47%
“…The lack of significant association observed between DM and DR-TB treatment outcome is consistent with findings from studies conducted in other countries, such as Georgia, Peru, Mexico and China. [11][12][13][14] However, studies in South Korea, Taiwan and Brazil have reported an association of DM with unfavourable outcomes. [7][8][9] These studies also report that unfavourable outcomes were significantly associated with poor glycaemic controls and other comorbidities caused by DM, such as chronic renal diseases, cardiovascular diseases and cerebrovascular diseases in patients with DM.…”
Section: Discussionmentioning
confidence: 99%
“…47 In diabetic patients, there is more severe pulmonary disease radiologically and bacteriologically, more adverse drug effects, delayed smear and culture conversion, and unfavourable 1-year outcome with higher mortality. 49 DM has been associated with treatment failure, relapse and drug resistance in some studies, 48 However, with prolonged treatment duration of 9 months for TB patients with DM in Hong Kong, the relapse rate was not found to be significantly increased. 49 Despite the large cohort size, no association was seen between DM and bacillary resistance to isoniazid or rifampicin, likely due to the good programmatic performance locally.…”
Section: Smoking and Dm As Important Co-morbid Conditions Of Tb In Olmentioning
confidence: 99%
“…Furthermore, DM is predominantly associated with pulmonary TB, rather than extra‐pulmonary disease . In diabetic patients, there is more severe pulmonary disease radiologically and bacteriologically, more adverse drug effects, delayed smear and culture conversion, and unfavourable 1‐year outcome with higher mortality . DM has been associated with treatment failure, relapse and drug resistance in some studies, However, with prolonged treatment duration of 9 months for TB patients with DM in Hong Kong, the relapse rate was not found to be significantly increased .…”
Section: Smoking and Dm As Important Co‐morbid Conditions Of Tb In Olmentioning
confidence: 99%
“…Increasing evidence is now available to show the substantial impact of host factors (e.g. smoking, diabetes mellitus, HIV, pharmacokinetics and pharmacogenetics) and disease characteristics (e.g. cavity, baseline and/or 2‐month smear/culture status) on various aspects of treatment outcomes.…”
Section: National Tb Control Strategy: Standardized Versus Individualmentioning
confidence: 99%